3D Synthetic Microstructures Fabricated by Two‐Photon Polymerization Promote Homogeneous Expression of NANOG and ESRRB in Mouse Embryonic Stem Cells. Issue 6 (21st January 2021) - Bakhtina, Natalia A.; Müller, Madlen; Wischnewski, Harry; Arora, Rajika; Ciaudo, Constance
Abstract: The development of in vitro models, which accurately recapitulate early embryonic development, is one of the fundamental challenges in stem cell research. Most of the currently employed approaches involve the culture of embryonic stem cells (ESCs) on 2D surfaces. However, the monolayer nature of these cultures does not permit cells to grow and proliferate in realistic 3D microenvironments, as in an early embryo. In this paper, novel 3D synthetic microstructure arrays, fabricated by two‐photon polymerization photolithography, are utilized to mimic tissue‐specific architecture, enabling cell‐to‐matrix interaction and cell‐to‐cell communication in vitro. Mouse ESCs (mESCs) are able to grow and proliferate on these structures and maintain their pluripotent state. Furthermore, the 3D microstructure arrays are integrated into a microscopy slide allowing the evaluation of the expression of key pluripotency factors at the single cell level. Comparing 2D and 3D surfaces, mESCs grown in serum + leukemia inhibitory factor on 3D microstructures exhibit a stronger signal intensity of three pluripotency markers—homeobox protein NANOG, octamer‐binding transcription factor 4, and estrogen‐related receptor beta (ESRRB)—and more homogenous expression of NANOG and ESRRB, than cells cultivated in 2i medium, demonstrating that 3D microstructures capture naïve pluripotency in vitro. Thus, the slide affords a novel and unique tool to model and study early development. Abstract : Novel 3D printed microplatform for maintenance of mouse embryonic stem cells are reported. The truly 3D environment of these arrays allows the proliferation of the cell population. Interestingly, this 3D culture system promotes naïve pluripotency as shown by the homogenous expression of NANOG and ESRRB, two key pluripotency factors.